The current and potential uses of legumes in various agroforestry systems in Malaysia. - Awang, Kamis; Ahmad, Abdul Manap (1981)
The paper reviews the current usage of legumes in various agro-forestry sytem including agri-silvicultural, silvo-pastoral, agro-silvo-pastoral and multipurpose forest tree system in Malaysia. It highlights the roles of legumes as cover crops, agricultural cash crops, fodder and forage, shade, timber and multipurpose trees. It also explores the potential of greater use of legumes through wider and more extensive application of agroforestry concept. The implications of this are discussed from the management, biological and socio-economic points of view.